THE EFFECT OF TASTE, LAYOUT AND WORD OF MOUTH ON PURCHASE DECISIONS IN BEEJE COFFEE LHOKSEUMAWE - Martina; Cut Sukmawati; Nanda Ameliany; Teuku Zulkarnaen; Lisa Iryani (PT. Radja Intercontinental Publishing, 2026)
This thesis examines the influence of taste, layout, and word of mouth on purchasing decisions at Beeje Coffee in Lhokseumawe. This is a quantitative study using a survey method and printed questionnaires distributed to 96 customers of Beeje Coffee in Lhokseumawe. The data analysis methods include instrument tests, classical assumption tests, and multiple linear regression analysis using SPSS version 25. The results indicate that taste (X1) has a positive and significant effect on purchasing decisions, with t = 2.218 and p = 0.029. Layout (X2) has a positive and significant effect, with t = 6.525 and p < 0.001. Word of mouth (X3) also has a positive and significant effect, with t = 3.870 and p < 0.001. Simultaneously, taste, layout, and word of mouth affect purchasing decisions, with F = 23.880 and p < 0.001. These findings show that product taste, spatial arrangement, and consumer recommendations contribute to purchasing decisions at Beeje Coffee.